Teacher’s Perspectives and Challenges towards English as a Medium of Instruction (EMI) - Ulfah Oktaviani (Jurnal Bahasa dan Sastra, 2019)
Abstract: Globalization has triggered the use of English in all aspects of life among others communication, technology, media, business, and academia. This leads to the increasing number of institutions around the world to use English as a Medium of Instruction (EMI)      in their classroom practices. However, there are many controversies among teachers in the implementation of EMI in teaching content subject. These pros and cons are caused by the challenges that teachers faced such as their quality, guidelines, resources, and student’s English proficiency. This paper aims to describe teacher’s perspectives and challenges towards the implementation of English as a Medium of instruction. Keywords: English as a Medium of instruction (EMI), controversies, perspectives, and challenges. Abstrak: Globalisasi telah memicu pengunaan Bahasa Inggris di segala aspek kehidupan seperti komunikasi, teknologi, media, bisnis, dan dunia akademik. Hal ini juga menyebabkan peningkatan jumlah institusi di dunia yang mengunakan Bahasa Inggris sebagai bahasa pengantar dalam proses belajar mengajar. Akan tetapi ada banyak kontroversi di antara guru dalam penerapan Bahasa Inggris sebagai bahasa pengantar dalam mengajar di kelas. pro dan kontra ini disebabkan oleh tantangan yang di hadapi guru seperti kualitas guru bimbingan kelas, pedoman, sumber daya, dan kesulitan bahasa. Artikel ini bertujuan untuk menjelaskan perspektif guru dan tantangan yang di hadapi guru dalam penerapan Bahasa Inggris sebagai bahasa pengantar di kelas. Kata-kata kunci: Bahasa Inggris sebagai bahasa pengantar, kontroversi, perspektif, dan tantangan